Agricultural Robot - G. , Suryanaga Raju; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Firstly, for any AGRI robot, the location is the priority because, on the basis of the location, the robot will work in the fixed area to work. Secondary is path deduction in crops. There are ROWs to detect those rows. We need the path deduction in the path deduction. We need image processing techniques for the high efficiency of the yield crop. For this, we need the autonomous robot of the farming process, saving the time and energy required for performing repetitive farming tasks and increasing the productivity of yield by treating every crop individually using the precision farming concept. The experiment demonstrates that the proposed method has efficiency and detection accuracy. Coverage of a partially known workshop for information gathering is the core problem for several applications, such as search and rescue precision agriculture and monitoring of critical infrastructures. The planning efficiency dynamically.